A high-elastic moisture-absorbing antistatic composite fiber and its preparation method

By combining polypropylene glycol terephthalate and polyethylene terephthalate and adding specific additives and nano-inorganic particles, highly elastic hygroscopic antistatic composite fibers are solved, and the existing composite fibers have poor performance in moisture absorption, breathability and antistatic, achieving higher fiber performance and durability.

CN119753886APending Publication Date: 2025-04-04HANGZHOU HUIFENG CHEM FIBRE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411892701.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing composite fibers do not perform well in moisture absorption, breathability and antistatic, and enhance performance by surface treatment or additives can easily lead to fragile fiber structures and reduce durability and strength.

Method used

Polypropylene glycol terephthalate and polyethylene terephthalate are combined, and nano-inorganic particles, sericin, sulfonate-based hydrophilic modifier and polyetherester antistatic agent are added to prepare highly elastic, hygroscopic antistatic composite fibers through spinning formation and heat setting processes.

Benefits of technology

On the basis of maintaining the original strength of the fiber, the elasticity, antistatic and hygroscopic properties of the composite fiber are significantly improved, and the mechanical properties and durability of the fiber are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201014960000071
    Figure BDA0005201014960000071
  • Figure BDA0005201014960000081
    Figure BDA0005201014960000081
Patent Text Reader

Abstract

The present application relates to the field of textile technology, and specifically discloses a high-elastic hygroscopic antistatic composite fiber and a preparation method thereof; a high-elastic hygroscopic antistatic composite fiber, comprising the following raw materials in parts by weight: 20-40 parts of polytrimethylene terephthalate, 60-80 parts of polyethylene terephthalate, 10-18 parts of nano inorganic particles, 5-8 parts of sericin, 5-10 parts of sulfonic acid hydrophilic modifier, 3-5 parts of polyether ester antistatic agent, 5-8 parts of carbon nanotubes, and 1-3 parts of surfactant; the polyether ester antistatic agent is preliminarily prepared into an antistatic masterbatch with carbon nanotubes; by combining polytrimethylene terephthalate and polyethylene terephthalate, under the synergistic effect of other components, the elasticity, antistatic and hygroscopic properties of the composite fiber can be improved on the basis of maintaining the original strength of the fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of textile technology, and in particular to a high-elasticity, moisture-absorbing and antistatic composite fiber and a preparation method thereof. Background Art

[0002] Composite fiber materials on the market are widely used in clothing, home textiles and other industries, but most fiber products lack good elasticity and hygroscopicity, especially in sportswear, underwear and other fields. Consumers have increasing requirements for fiber comfort, moisture absorption and perspiration function and anti-static performance. Polytrimethylene terephthalate (PTT) is widely used in textiles because of its high resilience, while polyethylene terephthalate (PET) has the advantages of high strength and stability. How to combine the advantages of these two materials, give it higher elasticity and better hygroscopicity while ensuring fiber strength, and overcome the static electricity problem that is common in synthetic fibers is a common problem in the industry.

[0003] Although traditional PTT / PET composite fibers have certain elasticity and wear resistance, they perform poorly in terms of moisture absorption, breathability and anti-static properties. Currently, the moisture absorption and anti-static properties of fibers are often enhanced mainly through surface treatment or the addition of additives, but these methods can easily lead to the brittle structure of the composite fibers and reduce the durability and strength of the composite fibers. Summary of the invention

[0004] In order to improve the hygroscopicity and antistatic properties of composite fibers, the present application provides a high-elastic hygroscopic and antistatic composite fiber and a preparation method thereof.

[0005] In the first aspect, the present application provides a highly elastic, hygroscopic and antistatic composite fiber, which adopts the following technical solution: A high-elastic hygroscopic antistatic composite fiber comprises the following raw materials in parts by weight: 20-40 parts of polytrimethylene terephthalate, 60-80 parts of polyethylene terephthalate, 10-18 parts of nano inorganic particles, 5-8 parts of sericin, 5-10 parts of sulfonic acid hydrophilic modifier, 3-5 parts of polyether ester antistatic agent, 5-8 parts of carbon nanotubes, and 1-3 parts of surfactant; the polyether ester antistatic agent is prepared into antistatic masterbatch with carbon nanotubes in advance.

[0006] By adopting the above technical solution, adding an appropriate amount of sericin and sulfonic acid hydrophilic modifier to the composite fiber raw material has good hygroscopicity and biocompatibility, which can make the composite fiber surface more easily absorb moisture, improve the hygroscopicity of the composite fiber, and make the composite fiber softer and more comfortable. The polyether ester antistatic agent and carbon nanotubes are made into antistatic masterbatch, which can be evenly dispersed in the composite fiber system, effectively reducing the surface resistance of the fiber and preventing static electricity accumulation. The polyether ester antistatic agent improves the conductivity of the fiber by forming a conductive layer on the fiber surface, thereby reducing static electricity and improving the antistatic performance of the composite fiber.

[0007] Polytrimethylene terephthalate has good flexibility and elasticity, and the high crystallinity and rigid molecular chain of polyethylene terephthalate can make the composite fiber have good mechanical properties and dimensional stability. The combination of polytrimethylene terephthalate and polyethylene terephthalate can improve the elasticity, antistatic and moisture absorption properties of the composite fiber while maintaining the original strength of the fiber.

[0008] Preferably, the polyethylene terephthalate comprises the following raw materials in parts by weight: 15-25 parts of terephthalic acid, 20-30 parts of ethylene glycol, 1-3 parts of a catalyst, 1-3 parts of a stabilizer, 5-10 parts of oxalic acid glutaramide, and 3-5 parts of pentamethylenediamine oxalate.

[0009] By adopting the above technical solution, pentamethylenediamine oxalate and oxalic acid glutaramide are introduced into the polyethylene terephthalate macromolecular chain, which can reduce the uniformity of the macromolecular chain, make it easier for water molecules to diffuse into the fiber macromolecules, and thus improve the hygroscopicity of the composite fiber. Oxalic acid glutaramide has more methylene flexible segments, which can improve the softness and elasticity of the composite fiber.

[0010] Preferably, the catalyst is antimony glycol and the stabilizer is triphenyl phosphite.

[0011] Preferably, the nano inorganic particles are at least one of nano zinc oxide and nano calcium carbonate.

[0012] By adopting the above technical solutions, nano zinc oxide can effectively absorb ultraviolet rays, provide ultraviolet protection for fibers, have good antibacterial properties, can inhibit the growth of bacteria and fungi, and can synergize with polyether ester antistatic agents to improve the conductivity of composite fibers, help reduce static electricity accumulation, and improve the durability and antistatic properties of composite fibers. Nano calcium carbonate can improve the hygroscopicity of composite fibers, make the fibers softer and more comfortable, and improve the hydrophilicity of the fibers. By adding nano zinc oxide and nano calcium carbonate, the mechanical strength, wear resistance and tensile strength of the composite fibers can be enhanced, and the problem of easy charging of composite fibers can be improved in synergy with antistatic agents.

[0013] Preferably, the sulfonic acid-based hydrophilic modifier is at least one of sodium benzenesulfonate, 5-sulfosalicylic acid, and 2-acrylamide-2-methylpropanesulfonic acid.

[0014] By adopting the above technical solution, sodium benzenesulfonate, 5-sulfosalicylic acid, and 2-acrylamide-2-methylpropanesulfonic acid contain sulfonic acid groups, which can form hydrogen bonds with water molecules. The introduction of sulfonic acid groups on the surface of the composite fiber can increase the hydrophilicity of the fiber, making it easier for the fiber to absorb and retain moisture. At the same time, the sulfonic acid group has a negative charge, which can improve the conductivity of the composite fiber. The negative charge on the fiber surface can neutralize the positive charge, thereby reducing static electricity accumulation and improving the antistatic performance of the fiber.

[0015] In a second aspect, the present application provides a method for preparing a highly elastic, hygroscopic and antistatic composite fiber, using the following technical solution: A method for preparing a highly elastic, hygroscopic and antistatic composite fiber comprises the following specific steps: The polyethylene terephthalate and the surfactant are equally divided into two parts, one part of the surfactant is made into a surfactant aqueous solution, the carbon nanotubes are mixed with the surfactant aqueous solution, ultrasonically dispersed, and dried to obtain the surface-treated carbon nanotubes, and then the carbon nanotubes are mixed with the molten polyether ester antistatic agent, ground after cooling, and then mixed with one part of the polyethylene terephthalate, and granulated after vacuum drying to obtain the antistatic masterbatch; Polypropylene terephthalate, nano inorganic particles, sericin, sulfonic acid hydrophilic modifier, antistatic masterbatch, remaining polyethylene terephthalate and surfactant are mixed, dried and heated to melt, the molten mixture is spun to form primary fibers, and the primary fibers are drawn and heat-set to form composite fibers.

[0016] By adopting the above technical scheme, the surface-treated carbon nanotubes are pre-dispersed in the molten polyether ester antistatic agent and combined with the polyethylene terephthalate matrix to prepare the antistatic masterbatch, so that the polyether ester antistatic agent and the carbon nanotubes are evenly dispersed in the composite fiber system, and multiple, uniform and continuous conductive paths can be formed in the fibers. While maintaining the good strength of the composite fiber, the composite fiber is enabled to have better antistatic properties.

[0017] Preferably, the method comprises the following specific steps: mixing terephthalic acid and ethylene glycol, adding a catalyst and a stabilizer to react at 230-250° C., then adding oxalic acid glutaramide and pentamethylenediamine oxalate, and continuing to heat to 255-280° C. to carry out a condensation reaction to obtain polyethylene terephthalate.

[0018] Preferably, the method comprises the following specific steps: The polyethylene terephthalate and the surfactant are equally divided into two parts, one part of the surfactant is made into a surfactant aqueous solution, the carbon nanotubes and the surfactant aqueous solution are mixed, ultrasonically dispersed, and dried to obtain the surface-treated carbon nanotubes, and then the carbon nanotubes are mixed with the molten polyether ester antistatic agent, ground after cooling, and then mixed with nano inorganic particles and a part of the polyethylene terephthalate, and granulated after vacuum drying to obtain the PET composite masterbatch; Mixing poly(trimethylene terephthalate), nano inorganic particles, sericin, sulfonic acid hydrophilic modifier, PET composite masterbatch with remaining polyethylene terephthalate and surfactant, heating and melting after drying, spinning the molten mixture to form primary fibers, and drawing and heat-setting the primary fibers to form composite fibers; The composite fiber is placed in an acetic acid solution, immersed at 40-60° C. for 1-2 hours, and then the composite fiber is taken out, washed with water, and vacuum dried to obtain a modified composite fiber.

[0019] By adopting the above technical solution, the nano inorganic particles are first made into PET masterbatch, so that the nano inorganic particles can be evenly dispersed in the fiber raw material system, so that the fiber can maintain uniform mechanical strength. At the same time, the prepared composite fiber is subjected to acid treatment, so that part of the nano inorganic particles can be acid-dissolved, thereby forming fine holes on the surface of the composite fiber, thereby improving the hydrophilic and hygroscopic properties of the composite fiber.

[0020] In summary, this application has the following beneficial effects: 1. Since the present invention makes the polyether ester antistatic agent and carbon nanotubes into antistatic masterbatch, the antistatic component is evenly dispersed in the composite fiber system, thereby improving the antistatic performance of the composite fiber. Adding an appropriate amount of sericin and sulfonic acid hydrophilic modifier to the composite fiber raw material makes it easier for the composite fiber surface to absorb water, thereby improving the hygroscopicity of the composite fiber. The combination of polypropylene terephthalate and polyethylene terephthalate can improve the elasticity, antistatic and hygroscopicity of the composite fiber while maintaining the original strength of the fiber.

[0021] 2. In the present application, pentamethylenediamine oxalate and oxalic acid glutaramide are introduced into the polyethylene terephthalate macromolecular chain to facilitate the diffusion of water molecules into the fiber macromolecules, thereby increasing the hygroscopicity of the composite fiber and improving the softness and elasticity of the composite fiber. DETAILED DESCRIPTION

[0022] The present application is further described in detail below with reference to the embodiments.

[0023] All raw materials in the examples are commercially available. Example

[0024] Example 1 This embodiment provides a high elastic moisture absorption antistatic composite fiber, comprising the following raw materials in parts by weight: 30 kg of polytrimethylene terephthalate, 70 kg of polyethylene terephthalate, 14 kg of nano inorganic particles, 7 kg of sericin, 8 kg of sulfonic acid hydrophilic modifier, 4 kg of polyether ester antistatic agent, 7 kg of carbon nanotubes, and 2 kg of surfactant. The nano inorganic particles are nano calcium carbonate, the average particle size of the nano inorganic particles is 50-80 nm, the sulfonic acid hydrophilic modifier is sodium benzene sulfonate, the polyether ester antistatic agent model is antistatic agent TXP-10, the surfactant is SDS, the intrinsic viscosity of polyethylene terephthalate is 0.6 dl / g, and the CAS number of polytrimethylene terephthalate is 26590-75-0.

[0025] A method for preparing a highly elastic, hygroscopic and antistatic composite fiber comprises the following specific steps: S1: Divide polyethylene terephthalate and a surfactant into two parts, prepare one part of the surfactant into a surfactant aqueous solution with a concentration of 15%, disperse carbon nanotubes in the surfactant aqueous solution, ultrasonically disperse for 30 minutes, and obtain surface-treated carbon nanotubes after drying, heat and melt the polyether ester antistatic agent, then mix the carbon nanotubes with the molten polyether ester antistatic agent, stir evenly, cool and grind, and then mix with one part of the polyethylene terephthalate, vacuum dry at room temperature for 6 hours, melt-extrude and granulate at 260°C to obtain an antistatic masterbatch.

[0026] S2: Mix poly(trimethylene terephthalate), nano-inorganic particles, sericin, sulfonic acid-based hydrophilic modifier, antistatic masterbatch with the remaining polyethylene terephthalate and surfactant, heat and melt them at 270°C, spin the molten mixture to form primary fibers, stretch the primary fibers, and heat-set them at 120°C to form composite fibers.

[0027] Example 2 The difference between Example 2 and Example 1 is that the amount of polytrimethylene terephthalate used in the high-elastic hygroscopic antistatic composite fiber raw material is 20 kg, the amount of polyethylene terephthalate used is 80 kg, the amount of nano inorganic particles used is 10 kg, the amount of sericin used is 8 kg, the amount of sulfonic acid hydrophilic modifier used is 5 kg, the amount of polyether ester antistatic agent used is 3 kg, the amount of carbon nanotubes used is 8 kg, and the amount of surfactant used is 3 kg.

[0028] Example 3 The difference between Example 3 and Example 1 is that the amount of polytrimethylene terephthalate used in the high-elastic hygroscopic antistatic composite fiber raw material is 40 kg, the amount of polyethylene terephthalate used is 60 kg, the amount of nano inorganic particles used is 18 kg, the amount of sericin used is 5 kg, the amount of sulfonic acid hydrophilic modifier used is 10 kg, the amount of polyether ester antistatic agent used is 5 kg, the amount of carbon nanotubes used is 5 kg, and the amount of surfactant used is 1 kg.

[0029] Example 4 The difference between Example 4 and Example 1 is that the polyethylene terephthalate comprises the following raw materials in parts by weight: 20 kg of terephthalic acid, 25 kg of ethylene glycol, 2 kg of catalyst, 2 kg of stabilizer, 8 kg of oxalic acid glutaramide, and 4 kg of pentamethylenediamine oxalate, wherein the catalyst is antimony ethylene glycol, the stabilizer is triphenyl phosphite, and the pentamethylenediamine oxalate is PA56.

[0030] A method for preparing a highly elastic, hygroscopic and antistatic composite fiber comprises the following specific steps: S1: terephthalic acid and ethylene glycol are mixed, a catalyst and a stabilizer are added, and the mixture is reacted at 240° C., and then oxalic acid glutaramide and pentamethylenediamine oxalate are added, and the mixture is heated to 270° C. for polycondensation reaction to obtain polyethylene terephthalate.

[0031] S2: Weigh polyethylene terephthalate and surfactant in proportion and divide them into two parts equally, make one part of the surfactant into a surfactant aqueous solution with a concentration of 15%, disperse carbon nanotubes in the surfactant aqueous solution, ultrasonically disperse for 30 minutes, and obtain surface-treated carbon nanotubes after drying, heat and melt the polyether ester antistatic agent, then mix the carbon nanotubes with the molten polyether ester antistatic agent, stir evenly, cool and grind, and then mix with one part of the polyethylene terephthalate, vacuum dry at room temperature for 6 hours, melt-extrude and granulate at 260°C to obtain an antistatic masterbatch.

[0032] S3: Mix poly(trimethylene terephthalate), nano-inorganic particles, sericin, sulfonic acid-based hydrophilic modifier, antistatic masterbatch with the remaining polyethylene terephthalate and surfactant, and dry them, heat and melt them at 270°C, spin the molten mixture to form primary fibers, stretch the primary fibers, and heat-set them at 120°C to form composite fibers.

[0033] Example 5 The difference between Example 5 and Example 4 is that the amount of terephthalic acid used in the polyethylene terephthalate raw material is 15 kg, the amount of ethylene glycol used is 30 kg, the amount of catalyst used is 1 kg, the amount of stabilizer used is 3 kg, the amount of oxalic acid glutaramide used is 5 kg, and the amount of pentamethylenediamine oxalate used is 5 kg.

[0034] Example 6 The difference between Example 6 and Example 4 is that the amount of terephthalic acid used in the polyethylene terephthalate raw material is 25 kg, the amount of ethylene glycol used is 20 kg, the amount of catalyst used is 3 kg, the amount of stabilizer used is 1 kg, the amount of oxalic acid glutaramide used is 10 kg, and the amount of pentamethylenediamine oxalate used is 3 kg.

[0035] Example 7 The difference between Example 7 and Example 4 is that the sulfonic acid-based hydrophilic modifier in the high-elastic hygroscopic antistatic composite fiber raw material is a mixture of 2-acrylamide-2-methylpropane sulfonic acid and 5-sulfosalicylic acid, and the mass ratio of 2-acrylamide-2-methylpropane sulfonic acid to 5-sulfosalicylic acid is 1:1.

[0036] Example 8 The difference between Example 8 and Example 7 is that the nano inorganic particles in the raw material of the high elastic hygroscopic antistatic composite fiber are a mixture of nano zinc oxide and nano calcium carbonate, and the mass ratio of nano zinc oxide to nano calcium carbonate is 1:1.

[0037] Example 9 The difference between Example 9 and Example 8 is that a method for preparing a highly elastic, hygroscopic and antistatic composite fiber comprises the following specific steps: S1: terephthalic acid and ethylene glycol are mixed, a catalyst and a stabilizer are added, and the mixture is reacted at 240° C., and then oxalic acid glutaramide and pentamethylenediamine oxalate are added, and the mixture is heated to 270° C. for polycondensation reaction to obtain polyethylene terephthalate.

[0038] S2: Weigh polyethylene terephthalate and a surfactant in proportion and divide them into two parts equally, prepare one part of the surfactant into a surfactant aqueous solution with a concentration of 15%, disperse carbon nanotubes in the surfactant aqueous solution, ultrasonically disperse for 30 minutes, and obtain surface-treated carbon nanotubes after drying, heat and melt the polyether ester antistatic agent, then mix the carbon nanotubes with the molten polyether ester antistatic agent, stir evenly, cool and grind, then mix with nano inorganic particles and one part of the polyethylene terephthalate, vacuum dry at room temperature for 6 hours, melt-extrude and granulate at 260°C to obtain PET composite masterbatch.

[0039] S3: Mix poly(trimethylene terephthalate), nano-inorganic particles, sericin, sulfonic acid-based hydrophilic modifier, PET composite masterbatch with the remaining polyethylene terephthalate and surfactant, and dry them, heat and melt them at 270°C, spin the molten mixture to form primary fibers, stretch the primary fibers, and heat-set them at 120°C to form composite fibers.

[0040] S4: putting the composite fiber into an acetic acid aqueous solution with a concentration of 90% at 50° C. for 1.5 hours, taking out the composite fiber, washing it with water, and vacuum drying it at 60° C. for 4 hours to obtain a modified composite fiber.

[0041] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no carbon nanotubes are used in the raw material of the high-elastic hygroscopic antistatic composite fiber.

[0042] A method for preparing a highly elastic, hygroscopic and antistatic composite fiber comprises the following specific steps: Poly(trimethylene terephthalate), nano-inorganic particles, sericin, sulfonic acid-based hydrophilic modifier, polyether ester antistatic agent, polyethylene terephthalate and surfactant are mixed and dried, heated to melt at 270°C, and the molten mixture is spun to form primary fibers. The primary fibers are drawn and heat-set at 120°C to form composite fibers.

[0043] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that only polytrimethylene terephthalate and polyethylene terephthalate are used in the raw materials of the high-elastic hygroscopic antistatic composite fiber.

[0044] A method for preparing a highly elastic, hygroscopic and antistatic composite fiber comprises the following specific steps: Polypropylene terephthalate and polyethylene terephthalate are mixed and dried, heated and melted at 270°C, the molten mixture is spun to form primary fibers, the primary fibers are drawn, and heat-set at 120°C to form composite fibers.

[0045] Performance testing The following performance tests were conducted on the highly elastic, hygroscopic and antistatic composite fibers provided in Examples 1-9 and Comparative Examples 1-2 of the present application. The specific test results are shown in Table 1.

[0046] Detection Methods 1. Hydrophilic and hygroscopic properties The moisture absorption effect of the composite fiber prepared in the present application was tested with reference to the standard of GB / T21655.1-2008 "Evaluation of Moisture Absorption and Quick-drying Properties of Textiles Part 1".

[0047] 2. Strength The mechanical properties of the composite fiber prepared in this application were tested using an XL-1A yarn tensile tester. Test method: The sample is introduced into the tension disk and the yarn guide wheel through the yarn guide hook, and passed downward through the upper and lower clamps to ensure that the sample is straightened without relaxation, and a pre-tension of about 10 cN is applied; the lower clamp drives the sample down until the sample breaks and then returns to its original position to obtain the breaking strength, breaking elongation and elastic modulus of the sample. The clamping distance is 250 mm, the stretching speed is 250 mm / min, and each sample is tested more than 10 times, and the results are averaged.

[0048] 3. Antistatic performance The volume resistivity of the composite fiber prepared in this application was tested using a YG321 fiber resistivity meter (Changzhou Textile Instrument Factory).

[0049] Table 1: Performance test results data table It can be seen from the performance test results that the composite fiber prepared in the present application can improve the elasticity, antistatic and hygroscopic properties of the composite fiber while maintaining the original strength of the fiber by combining poly(trimethylene terephthalate), polyethylene terephthalate and other components. By comparing Comparative Examples 1-2 with Example 1, it can be seen that Comparative Example 1 does not use carbon nanotubes, and Comparative Example 2 only uses poly(trimethylene terephthalate) and polyethylene terephthalate to make fibers. It can be seen from the performance test results that the comprehensive performance of the composite fiber will decrease. Although the use of polyether ester antistatic agent in Comparative Example 1 still maintains a certain antistatic effect, the dispersion and compatibility effect of the polyether ester antistatic agent in Comparative Example 1 with the matrix is ​​limited, and the antistatic of the composite fiber is unevenly dispersed in the composite fiber system, and a continuous conductive path cannot be formed, thereby affecting the strength and antistatic effect of the composite fiber.

[0050] By comparing Examples 4-7 with Example 1, it can be seen that the modification of polyethylene terephthalate with pentamethylenediamine oxalate and oxalic acid glutaramide can enhance the moisture absorption effect and flexibility of the composite fiber, thereby improving the antistatic effect of the composite fiber.

[0051] It can be seen from Example 9 that by first making the nano-inorganic particles into PET masterbatch and then subjecting the prepared composite fiber to acid treatment, it can be seen from the performance test results that the moisture absorption of the composite fiber is significantly increased, which further illustrates that by combining the nano-inorganic particles with acid dissolution, tiny pores can be formed on the surface of the composite fiber, thereby improving the hygroscopicity of the composite fiber.

[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A highly elastic, hygroscopic and antistatic composite fiber, characterized in that: The invention comprises the following raw materials in parts by weight: 20-40 parts of polytrimethylene terephthalate, 60-80 parts of polyethylene terephthalate, 10-18 parts of nano inorganic particles, 5-8 parts of sericin, 5-10 parts of sulfonic acid hydrophilic modifier, 3-5 parts of polyether ester antistatic agent, 5-8 parts of carbon nanotubes and 1-3 parts of surfactant; the polyether ester antistatic agent is prepared into antistatic masterbatch with carbon nanotubes in advance.

2. The high elastic moisture-absorbing antistatic composite fiber according to claim 1, characterized in that: The polyethylene terephthalate comprises the following raw materials in parts by weight: 15-25 parts of terephthalic acid, 20-30 parts of ethylene glycol, 1-3 parts of a catalyst, 1-3 parts of a stabilizer, 5-10 parts of oxalic acid glutaramide, and 3-5 parts of pentamethylenediamine oxalate.

3. The high elastic moisture-absorbing antistatic composite fiber according to claim 2, characterized in that: The catalyst is antimony glycol, and the stabilizer is triphenyl phosphite.

4. The high elastic moisture-absorbing antistatic composite fiber according to claim 1, characterized in that: The nano inorganic particles are at least one of nano zinc oxide and nano calcium carbonate.

5. The high elastic moisture-absorbing antistatic composite fiber according to claim 1, characterized in that: The sulfonic acid-based hydrophilic modifier is at least one of sodium benzenesulfonate, 5-sulfosalicylic acid, and 2-acrylamide-2-methylpropanesulfonic acid.

6. A method for preparing the highly elastic, hygroscopic and antistatic composite fiber according to any one of claims 1 to 5, characterized in that: The specific steps include: The polyethylene terephthalate and the surfactant are equally divided into two parts, one part of the surfactant is made into a surfactant aqueous solution, the carbon nanotubes are mixed with the surfactant aqueous solution, ultrasonically dispersed, and dried to obtain the surface-treated carbon nanotubes, and then the carbon nanotubes are mixed with the molten polyether ester antistatic agent, ground after cooling, and then mixed with one part of the polyethylene terephthalate, and granulated after vacuum drying to obtain the antistatic masterbatch; Polypropylene terephthalate, nano inorganic particles, sericin, sulfonic acid hydrophilic modifier, antistatic masterbatch, remaining polyethylene terephthalate and surfactant are mixed, dried and heated to melt, the molten mixture is spun to form primary fibers, and the primary fibers are drawn and heat-set to form composite fibers.

7. The method for preparing the highly elastic, hygroscopic and antistatic composite fiber according to claim 6, characterized in that: The method comprises the following specific steps: mixing terephthalic acid and ethylene glycol, adding a catalyst and a stabilizer to react at 230-250° C., then adding oxalic acid glutaramide and pentamethylenediamine oxalate, and continuing to heat to 255-280° C. to carry out polycondensation reaction to obtain polyethylene terephthalate.

8. The method for preparing the highly elastic, hygroscopic and antistatic composite fiber according to claim 6, characterized in that: The specific steps include: The polyethylene terephthalate and the surfactant are equally divided into two parts, one part of the surfactant is made into a surfactant aqueous solution, the carbon nanotubes and the surfactant aqueous solution are mixed, ultrasonically dispersed, and dried to obtain the surface-treated carbon nanotubes, and then the carbon nanotubes are mixed with the molten polyether ester antistatic agent, ground after cooling, and then mixed with nano inorganic particles and a part of the polyethylene terephthalate, and granulated after vacuum drying to obtain the PET composite masterbatch; Mixing poly(trimethylene terephthalate), nano inorganic particles, sericin, sulfonic acid hydrophilic modifier, PET composite masterbatch with remaining polyethylene terephthalate and surfactant, heating and melting after drying, spinning the molten mixture to form primary fibers, and drawing and heat-setting the primary fibers to form composite fibers; The composite fiber is placed in an acetic acid solution, immersed at 40-60° C. for 1-2 hours, and then the composite fiber is taken out, washed with water, and vacuum dried to obtain a modified composite fiber.

Citation Information

Cited By

  • Anti-static fiber, anti-static textile and anti-static underwear prepared from anti-static fiber and anti-static textile

    CN121272591A